Persuasive Missionary Endeavor in The Story of Prophet Musa and Fir’aun: Study of Chapter Thaha Verse 44 - Fauziah, Mira (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2023)
Persuasive da'wah is a da'wah that is carried out in a gentle and warm way. Not all da'i can apply persuasive da'wah to their mad'unya. Some da'i still exist who preach using language that does not touch the heart. This paper aims to find out how persuasive preaching was carried out by the prophets Moses and Aaron against Fir'aun. This paper uses the countenance analysis method, which analyzes the meaning of Surah Thaha, verse 44, of the Qur'an using the theory of persuasive da'wah. The results showed that the Al-Quran Surah Thaha, verse 44, reveals the story of Prophet Moses and Prophet Aaron preaching to Pharaoh in a gentle way even though Pharaoh knew that he was a despotic king and disobeyed Allah. The term